Meningoencephalitis caused by Mycobacterium bovis in a calf. Case report - Favila-Humara, Lucia del Carmen (2021)
A clinical case of tuberculous meningoencephalitis in a 5-month-old Holstein calf that presented nervous symptoms is described. The calf was part of a herd with a 30% prevalence of tuberculosis. The animal was euthanized, and a necropsy was performed. No lesions were found in organs of the thoracic or abdominal cavity. Brain samples were taken for histopathology (hematoxylin-eosin and Zielh Nelsen staining), bacteriology and PCR-MRD1 studies. In the brain, macroscopic inflammatory lesions with congestion and granular appearance were observed in the meninges, as well as fibrous adhesions in the ventral area. Microscopically, inflammatory infiltrate, lymphocytes, macrophages, epithelioid cells, plasma cells and multinucleated giant cells, areas of central necrosis, dystrophic mineralization and acid-fast bacilli were observed. Granulomatous meningoencephalitis due to Mycobacterium bovis was confirmed by bacterial isolation and PCR-MRD1.